Brain plasticity of rats exposed to prenatal immobilization stress - Abrahamyan, S.S.; Meliksetyan, I.B.; Sahakyan, I.K.; Tumasyan, N.V.; Badalyan, B.Yu.; Galoyan, A.A. (Вiopolymers and Cell, 2011)
Aim. This histochemical and immunohistochemical study was aimed at examining the brain cellular structures
of newborn rats exposed to prenatal immobilization (IMO) stress. Methods. Histochemical method on detection
of Ca2+-dependent acid phosphatase activity and ABC immunohistochemical technique. Results. Cell structures
with radial astrocytes marker GFAP, neuroepithelial stem cell marker gene nestin, stem-cells marker and the
hypothalamic neuroprotective proline-rich polypeptide PRP-1 (aka Galarmin, a natural cytokine of a common
precursor to neurophysin vasopressin associated glycoprotein) have been revealed in several brain regions.
Conclusions. Our findings indicate the process of generation of new neurons in response to IMO and PRP-1
involvement in this recovery mechanism, as PRP-1-Ir was detected in the above mentioned cell structures, as
well as in the neurons and nerve fibers.
Keywords: rat brain plasticity, prenatal immobilization stress, GFAP-, nestin-, stem cells-, and PRP-1-immunoreactive structures. Мета даного гісто- та імуногістохімічного дослідження полягала у вивченні клітинних структур мозку новонароджених щурів
після дії внутрішньоутробного іммобілізаційного стресу (ІМО).
Методи. Гістохімічний метод виявлення активності Са2+
-залежної кислої фосфатази та АВС-імуногістохімічний метод. Результати. У різних відділах мозку у відповідь на ІМО визначено клітинні структури, які містять маркери радіальних астроцитів
GFAP, стовбурових клітин мишей, нейроепітеліальних стовбурових клітин нестину і гіпоталамічного нейропротекторного багатого на пролін поліпептиду, PRP-1 (природний цитокін під назвою
Галармін, попередником якого є нейрофізин-вазопресин-асоційований глікопротеїн). Висновки. Виявлення PRP-1 у вищезазначених
клітинних структурах поряд з нейронами і нервовими волокнами
вказує на процес утворення нових нейронів у відповідь на ІМО та
включення PRP-1 у механізм даного відновлювального процесу.
Ключові слова: пластичність мозку щурів, внутрішньоутробний іммобілізаційний стрес, імунореактивність стовбурових клітин PRP-1, GFAP і нестину. Цель данного гисто- и иммуногистохимического исследования
состояла в изучении клеточных структур мозга новорожденных
крыс, подвергшихся внутриутробному иммобилизационному
(ИМО) стрессу. Методы. Применены гистохимический метод
выявления активности Са2+
-зависимой кислой фосфатазы и АВС
иммуногистохимический метод. Результаты. В различных отделах мозга в ответ на ИМО определены клеточные структуры,
содержащие маркеры радиальных астроцитов GFAP, стволовых
клеток мышей, нейроэпителиальных стволовых клеток нестина
и гипоталамического нейропротекторного пролин-богатого полипептида, PRP-1 (природный цитокин под названием Галармин,
предшественником которого является нейрофизин-вазопрессин-ассоциированный гликопротеин). Выводы. Обнаружение
PRP-1 в вышеупомянутых клеточных структурах вместе с нейронами и нервными волокнами указывает на процесс образования
новых нейронов в ответ на ИМО и включение PRP-1 в механизм
данного восстановительного процесса.
Ключевые слова: пластичность мозга крыс, внутриутробный
иммобилизационный стресс, иммунореактивность стволовых
клеток PRP-1, GFAP и нестина.